1992
DOI: 10.1073/pnas.89.11.4820
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of human CREB-2: an ATF/CREB transcription factor that can negatively regulate transcription from the cAMP response element.

Abstract: The cAMP response element (CRE) is an octanucleotide motif (TGACGTCA) that mediates diverse transcriptional regulatory effects. In this report we describe the isolation and characterization of a full-length cDNA that encodes a CRE binding protein called CREB-2. Like other ATF/CREB transcription factors, the 351-amino acid CREB-2 protein contains a COOH-terminal leucine-zipper motif and an adjacent basic domain. CREB-2 mRNA is expressed ubiquitously in human tumor cell lines and mouse organs suggesting that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
202
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(211 citation statements)
references
References 33 publications
7
202
1
1
Order By: Relevance
“…35,36 ATF4 acts as a transcription activator and inhibitor. 35,[37][38][39][40] The results of our cytokine array assay revealed that ATF4 positively regulated the secretion of RANTES, sICAM-1, IL-6, IL-8 and IFN-c, all of which are proinflammatory cytokines. RANTES, a representative chemotactic factor, mediates T cell differentiation and cytokine release, and it is also a chemoattractant for blood monocytes, memory Thelper cells, mast leukocyte and eosinophils.…”
Section: Discussionmentioning
confidence: 90%
“…35,36 ATF4 acts as a transcription activator and inhibitor. 35,[37][38][39][40] The results of our cytokine array assay revealed that ATF4 positively regulated the secretion of RANTES, sICAM-1, IL-6, IL-8 and IFN-c, all of which are proinflammatory cytokines. RANTES, a representative chemotactic factor, mediates T cell differentiation and cytokine release, and it is also a chemoattractant for blood monocytes, memory Thelper cells, mast leukocyte and eosinophils.…”
Section: Discussionmentioning
confidence: 90%
“…Interference of the repressor function of CREMa by the DN CREB mutants could allow as yet unidenti®ed activator protein(s) to positively regulate AP-1 and CRE transcriptional activity in keratinocytes. Alternative targets of the A-CREB and KCREB mutants include CREB itself which exists in di erent phosphorylation states in keratinocytes and the transcriptional repressor, CREB-2 (Karpinski et al, 1992), that binds to the CRE without interacting with CRE activator proteins. Altering the ratios of activated and nonactivated forms of CREB through interactions with the DN constructs could result in di erences in the overall a b Figure 8 CREB family proteins repress AP-1 transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…The ATF4 (called CREB2 in this reference) expression plasmid (CMV-CREB2) was kindly provided by Dr. J. Leiden (Department of Medicine, University of Chicago, Chicago, IL, U.S.A.) [39]. The pCG-ATF3 expression vector was described previously [34].…”
Section: Plasmid and Oligonucleotide Constructionmentioning
confidence: 99%
“…The fulllength human clone was later isolated and named TAXREB67 [47] and CREB2 [39], while the mouse homologues are designated mATF4 [48], mTR67 [49] and C\EBP-related ATF (C\ATF) [50]. ATF4 has been demonstrated to activate transcription through interactions at ATF\CRE sites [39,46,48], and also through the interleukin-2 CD28 response element [51]. While there are reports showing that ATF4 can suppress promoter activity [52], others describe ' apparent ' transcriptional repression by ATF4 due to ' squelching ' under certain conditions [46].…”
Section: Atf4 and The Stress Responsementioning
confidence: 99%
See 1 more Smart Citation